Stratégies de gestion de la chaleur et performances sportives de haut niveau : éclairage psychophysiologique et recommandations appliquées - Robin, N.; Hermand, E.; Hatchi, V.; Hue, O. (Science & Sports, 2023)
Objectives This article sheds light on the different heat stress management strategies, common or innovative, in order to analyze those that would be the most suitable and effective for athletes who have to compete in humid and/or hot environments.